ANALISIS KLASIFIKASI EMOSI CINTA TOKOH LAYLĀ DALAM NOVEL AL-ARWĀHU AL-MUTAMARRIDAH KARYA KHALIL GIBRAN - Riztikha Khairani; Iin Suryaningsih (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2020)
The purpose of this study is to determine the character of the soul in the novel Al-arwa<hu Al-Mutamarridah by using the theory of David Krech. The research method used is descriptive qualitative content analysis techniques. The results of this study describe that there are three findings of the classification of the emotion of love that occurred in Laylā in the novel Al-arwāhu Al-Mutamarridah by Khalil Gibran with the theme Maḍja‘u Al-ūarūsi. David Krech's theory is related to the literary psychology of emotions which is divided into four parts, namely basic emotions, emotions related to sensory stimulation, emotions related to self-assessment, and emotions related to others. This theory is appropriate to dissect the emotional classification of the main character Laylā in the novel Al-arwāhu Al-Mutamarridah by Khalil Gibran with the theme Maḍja‘u Al-ūarūsi. This shows that the classification of emotions has been detailed by Krech as evidenced by novel quotations so this research confirms the existence of Krech's thoughts about emotions.